Styl urzędowy mieszkańców wsi na przykładzie podań do wybranych ośrodków pomocy społecznej w południowej Małopolsce - Piechnik, Anna (2019)
OFFICIAL STYLE OF VILLAGE INHABITANTS BASED ON THE EXAMPLES OF APPLICATIONS TO SELECTED SOCIAL SERVICE CENTRES IN SOUTHERN LESSER POLANDThe book presents an anthropological and cultural analysis of the official style of village inhabitants. Its source basis includes 869 applications written only by the authors and submitted to social service centres from six neighbouring communes located in the southern part of the Lesser Poland Voivodeship.Applications are a peripheral genre within the official style, in which most papers are created by an institution and directed to the citizens (or other institutions). However, such texts are especially representative of the communication between a citizen and the office. My research material includes applications written by the inhabitants of the Lesser Poland villages in the highlands of Ciężkowice-Rożnów, and it has made it possible for me to analyse the fulfilment of the official style by the people who rarely play the role of written information senders. The selection of a social service centre as the addressee of those papers resulted from my willingness to reach the authentic texts by people whose language was only slightly influenced by education or work (especially intellectual work) carried out outside the place of residence. Also, I found it interesting to check to what extent the local dialect influences written texts of those language users.
Keywords: official style; village; Lesser Poland; sociolinguistics; Polish language